Speech Tactics of Discrediting Strategy in the U.S. Diplomatic Discourse - Sudus, Yulia (East European Journal of Psycholinguistics, 2018)
The paper is focused on the study of the discrediting strategy, which is a linguistic and pragmatic feature of contemporary U.S. diplomatic discourse, namely, to speech tactics that contribute to its implementation in the discourse of the U.S. diplomats. Attention is drawn to the US diplomats’ speeches by V. Nuland, D. Baer, G. Pyatt and S. Power made in 2013 – 2015, and related to the military conflict in the eastern Ukraine. The object of the study is the U.S. diplomatic discourse, which contains speech tactics of discrediting strategy. The subject matter is the tactics of the U.S. diplomats aimed at implementing the discrediting strategy in their speeches on the eve of military conflict in the eastern Ukraine and during the phases of its aggravation. As it was revealed, discrediting strategy is one of the most powerful conflict strategies of the U.S. diplomats’ verbal behavior, which is implemented in their discourse by means of such tactics as: accusation, impersonal accusation, disclosure, “universal truth”, condemnation, threat, order, mentioning in a negative light, and contrast. Among the leading linguistic tactics of implementing the discrediting strategy in the U.S. diplomatic discourse are tactics of mentioning in a negative light and accusation. References D’Acquisto, G. (2017). Linguistic Analysis of Diplomatic Discourse: UN Resolutions on the Question of Palestine. UK : Cambridge Scolars Publishing. Donahue, R. (1997) Diplomatic Discourse: International Conflict at the United Nations. London : Greenwood Publishing Group. Gumperz, J. (1982). Discourse Strategies. Cambridge: CUP. McClellan, M. Public Diplomacy in the Context of Traditional Diplomacy. Retrieved from: http://www.publicdiplomacy.org/45.htm Newmann, I. (2002). Returning Practice to the Linguistic Turn: The Case of Diplomacy. Millenium: Journal of International Studies, 31(3), 627-651. Pratkanis, A. (2009). Public Diplomacy in International Conflicts. A Social Influence Analysis. Routledge Handbook of Public Diplomacy. California, 2009. Schuster, J. (2015). Diplomatic Discourse. Lulu.com. Scotto di Carlo G. (2015). “Weasel words” in legal and diplomatic discourse : vague nouns and phrases in UN resolutions relating to the second Gulf war. International Journal for the Semiotics of Law, 28(3), 559-576. Snow, N. (2009). Rethinking Public Diplomacy. Routledge Handbook of Public Diplomacy. London. Беляков М. Характер эмотивности дипломатического дискурса. Вестник Российского университета дружбы народов. Серия: Лингвистика, 2015. C. 124-131. Вебер Е. Опыт лингвистического исследования когнитивного диссонанса в английском дипломатическом дискурсе : автореф. дис. на соиск. науч. ст. канд. фил. наук : 10.02.04 «Германские языки». И., 2004. Голованова Д. Интердискурсивность дипломатического дискурса. Известия Волгоградского государственного педагогического университета. Сер. : Филологические науки, 2014, 7. C. 25-30. Зонова Т. Современная модель дипломатии. Истоки становления и перспективы развития. М.: РОССПЭН, 2003. Кащишин Н. Диференціація таксономічних одиниць англомовного дипломатичного дискурсу. Східноєвропейський журнал психолінгвістики, 2014, 1(2). C. 54-62. Кожетева А. Лингвопрагматические характеристики дипломатического дискурса [Электронный ресурс] : дис. на соиск. науч. ст. канд. филол. наук: спец. 10.02.19 «Теория языка». Москва, 2012. – Режим доступа : http://www.dissercat.com/content/ lingvopragmaticheskie-kharakteristiki-diplomaticheskogo-diskursa Мельник І. В. Типи комунікативних стратегій. Studia Linguistica, 2011, №5. C. 377-380. Судус Ю. Лінгвопрагматичні засоби реалізації стратегії дискредитації в американському дипломатичному мовленні (на матеріалі промов Дж. Р. Пайєтта). Вісник Львівського у-ту. Серія: Іноземні мови. Львів, 2016, №23. С. 47-56. Судус Ю. Мовленнєві засоби реалізації стратегії дискредитації в англомовному дипломатичному дискурсі. Актуальні питання іноземної філології. Луцьк: Східноєвроп. нац. ун-т ім. Лесі Українки, 2016, №5. С. 152-160. Судус Ю. Прагматичні засоби реалізації стратегії дискредитації в американському дипломатичному мовленні (на матеріалі промов Д. Б. Байєра). Науковий часопис НПУ імені М. П. Драгоманова. Київ, 2015, №13. С. 108-115. Судус Ю. “Weasel words” як один з прийомів реалізації стратегії дискредитації в англомовному дипломатичному дискурсі (на матеріалі промов С. Пауер, В. Нуланд, Д. Байєра, Дж. Пайєтта). Вісник Запорізького національного університету. Серія: філологія. – Запоріжжя, 2016, №1. С. 237-244. Терентий Л. Дипломатический дискурс как особая форма политической коммуникации. Вопросы когнитивной лингвистики. 2010, №1. С. 47-56. References (translated and transliterated) D’Acquisto, G. (2017). Linguistic Analysis of Diplomatic Discourse: UN Resolutions on the Question of Palestine. UK : Cambridge Scolars Publishing. Donahue, R. (1997) Diplomatic Discourse : International Conflict at the United Nations. London : Greenwood Publishing Group. Gumperz, J. (1982). Discourse Strategies. Cambridge : CUP. McClellan, M. Public Diplomacy in the Context of Traditional Diplomacy. Retrieved from http://www.publicdiplomacy.org/45.htm Newmann, I. (2002). Returning Practice to the Linguistic Turn : The Case of Diplomacy. Millenium : Journal of International Studies, 31(3), 627-651. Pratkanis, A. (2009). Public Diplomacy in International Conflicts. A Social Influence Analysis. Routledge Handbook of Public Diplomacy. California, 2009. Schuster, J. (2015). Diplomatic Discourse. Lulu.com. Scotto di Carlo G. (2015). “Weasel words” in legal and diplomatic discourse : vague nouns and phrases in UN resolutions relating to the second Gulf war. International Journal for the Semiotics of Law, 28(3), 559-576. Snow, N. (2009). Rethinking Public Diplomacy. Routledge Handbook of Public Diplomacy. London. Beliakov, M. (2015). Harakter emotivnosti diplomaticheskogo diskursa [The character of the diplomatic discourse’s emotiveness]. Vestnik Rossiyskogo Universiteta Druzhby Narodov. Seriia: Lingvistika, 124-131. Veber, Ie. (2004). Opyt lingvisticheskogo issledovaniya kognitivnogo dissonansa v anglijskom diplomaticheskom diskurse. [Experience of linguistic research of cognitive dissonance in English diplomatic discourse]. Extended Summary of Ph.D. dissertation. Irkutsk: Irkutsk State Linguistic University. Golovanova, D. (2014). Interdiskursivnost diplomaticheskogo diskursa [Interdiskursivity of diplomatic discourse]. Izvestiya Volgogradskogo Gosudarstvennogo Pedagogicheskogo Universiteta. Ser.: Filologicheskie Nauki, 7, 25-30. Zonova, T. (2003). Sovremennaya model diplomatii. Istoki stanovleniya i perspektivy razvitiya [Modern model of diplomacy. The origins and prospects of development]. Moscow: ROSSPEN. Kashchyshyn, N. (2014). Dyferentsiatsiia taksonomichnykh odynyts anhlomovnoho dyplomatychnoho dyskursu [Differentiation of taxonomic units of English-speaking diplomatic discourse], East European Journal of Psycholinguistics, 1(2), 54-62. Kozheteva, A. Lingvopragmaticheskie harakteristiki diplomaticheskogo diskursa [Linguistic and pragmatic peculiarities of diplomatic discourse]. Retrieved from: http://www.dissercat.com/ content/lingvopragmaticheskie-kharakteristiki-diplomaticheskogo-diskursa Melnyk, I. (2011). Typy komunikatyvnykh stratehii [Types of communicative strategies]. Studia Linguistica, 5, 377-380. Sudus, Yu. (2016). Linhvoprahmatychni zasoby realizatsii stratehii dyskredytatsii v amerykanskomu dyplomatychnomu movlenni (na materiali promov Dzh. R. Paiietta) [Linguopragmatic means of implementing of discrediting strategy in American diplomatic speech (based on the statements by G. Pyatt)]. Visnyk Lvivskoho Universytetu. Seriia: Inozemni Movy, 23, 47-56. Sudus, Yu (2016). Movlennievi zasoby realizatsii stratehii dyskredytatsii v anhlomovnomu dyplomatychnomu dyskursi [Language means of discrediting strategy implementation in English diplomatic discourse]. Aktualni Pytannia Inozemnoi Filolohii, 5, 152-160. Sudus, Yu (2015). Prahmatychni zasoby realizatsii stratehii dyskredytatsii v amerykanskomu dyplomatychnomu movlenni (na materiali promov D. B. Baiiera) [Pragmatic means of discrediting strategy implementation in the American diplomatic speech (based on the statements by D. Baer)]. Naukovyi chasopys NPU imeni M. P. Drahomanova, 13, 108-115. Sudus, Yu (2016). “Weasel words” yak odyn z pryiomiv realizatsii stratehii dyskredytatsii v anhlomovnomu dyplomatychnomu dyskursi (na materiali promov S. Pauer, V. Nuland, D. Baiiera, Dzh. Paiietta) ["Weasel words" as one of the methods of discrediting strategy implementation in the English-speaking diplomatic discourse (based on statements by S. Power, V. Nuland, D. Baer,G. Pyatt]. Visnyk Zaporizkoho Natsionalnoho Universytetu. Seriia: Filolohiia, 1, 237-244. Terentii, L. (2010). Diplomaticheskij diskurs kak osobaya forma politicheskoj kommunikacii [Diplomatic discourse as a special form of political communication]. Voprosy Kognitivnoy Lingvistiki, 1, 47-56. Sources Baer D. April 16, 2015. Retrieved from: http://ukraine.usembassy.gov/statements/osce-violations-04162015.html Nuland V. April 9, 2014. Retrieved from: http://ukraine.usembassy.gov/statements/nuland-ukraine-04092014.html Nuland V. January 27, 2015. Retrieved from: http://ukraine.usembassy.gov/statements/nuland-transatlantic-resolve-01272015.html Power, S. August 28, 2014. Retrieved from: http://www.washingtonpost.com/world/full-transcript-remarks-by-ambassador-samantha-power-us-permanent-representative-to-the-united-nations-at-a-security-council-session-on-ukraine/2014/08/28/b3f579b2-2ee8-11e4-bb9b-997ae96fad33_story.html Power S. March 19, 2014. Retrieved from: http://ukraine.usembassy.gov/statements/power-ukraine-03192014.html Pyatt G. April 24, 2015. Retrieved from: http://ukraine.usembassy.gov/speeches/pyatt-vox-ukraine-conf-04242015.html Pyatt G. January 31, 2014. Retrieved from: http://ukraine.usembassy.gov/statements/amb-ukraine.html